Effect of dopamine on inflammatory status in kidneys of brain-dead rats - Schaub, Meike; Plötz, Christian J.; Gerbaulet, Daniel; Fang, Liu; Kranich, Pia; Stadlbauer, Thomas H. W.; Göttmann, Uwe; Yard, Benito A.; Braun, Claude; Schnülle, Peter; Woude, Fokko J. van der (Transplantation, 2004)
BACKGROUND: Brain death has been identified as an independent risk factor for chronic allograft dysfunction. In two independent retrospective clinical studies, we showed that dopamine treatment of brain-dead donors improves long-term kidney graft survival. The mechanisms underlying the protective effects of dopamine treatment in vivo have not been identified. To elucidate the mechanisms underlying the protective effect of dopamine on kidneys of brain-dead donors, we studied a model for brain death in rats. METHODS: In F344 rats, brain death was induced by epidural inflation of a 3F Fogarty catheter. Apneic animals were mechanically ventilated, and clinically relevant dosages of dopamine (2, 6, 10, or 14 microg/kg/min) were given for 6 hr from the onset of brain death. Ventilated, non-brain-dead animals served as controls. RESULTS: Dopamine significantly reduced renal monocyte infiltration and major histocompatibility class II and P-selectin expression in brain-dead animals. It also prevented further up-regulation of the inflammatory markers tumor necrosis factor-alpha and monocyte chemoattractant peptide-1. Concomitantly, the presence of inducible anti-oxidant heme oxygenase-1, known for its cytoprotective effects, was strongly increased by dopamine. CONCLUSION: We identified several mechanisms underlying the protective effects of dopamine treatment on kidney grafts. The identification of these mechanisms may help to design more effective future strategies for treatment of cadaveric kidney donors.